2006
DOI: 10.1097/01.brs.0000224176.40457.52
|View full text |Cite
|
Sign up to set email alerts
|

Thoracolumbar Hemivertebrae Resection by Double Approach in a Single Procedure

Abstract: This procedure is safe and offers a persistent correction with a short segment fusion. Surgery should be performed as early as possible to avert severe local deformities and prevent secondary structural deformities in order to avoid extensive fusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
49
0
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(62 citation statements)
references
References 38 publications
5
49
0
8
Order By: Relevance
“…In the past two decades, many authors described hemivertebra excision by a combined anterior and posterior approach in one-or-two-stage procedures. Bollini [4] reported a long follow-up in cases of hemivertebra resection by a combined anterior and posterior approach performed in a single stage procedure. Ruf and Harms [5,6] used a hemivertebra resection by posterior resection only with transpedicular instrumentation in early correction even in very young patients; other authors have more recently described similar procedures [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In the past two decades, many authors described hemivertebra excision by a combined anterior and posterior approach in one-or-two-stage procedures. Bollini [4] reported a long follow-up in cases of hemivertebra resection by a combined anterior and posterior approach performed in a single stage procedure. Ruf and Harms [5,6] used a hemivertebra resection by posterior resection only with transpedicular instrumentation in early correction even in very young patients; other authors have more recently described similar procedures [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…a, b Preoperative photographs showed scoliosis with trunk tilt to left; c preoperative coronal Cobb angle was 102°; d bending Cobb angle was 87°; e preoperative thoracic kyphosis was 35°; f, g 3D-CT reconstruction showed that the UUB was located at vertebrae T6-7, T8-11 and L1-2; h postoperative coronary Cobb angle was 38°, with a correction rate of 63% and balanced coronal plane; i postoperative thoracic kyphosis was 27°; j, k the postoperative photographs showed good trunk balance; l, m no loss of correction was found in either the coronal or sagittal plane 2 years after the operation Eur Spine J (2012) 21:498-505 503 failures of formation. There have been a number of reports on the surgical management of scoliosis due to the presence of hemivertebrae and most authors have reported good clinical results [1,9,10]. The incidence of scoliosis due to failure of segmentation is not known.…”
Section: Discussionmentioning
confidence: 99%
“…The early diagnosis and treatment of these congenital deformities by resection and short level fusion appears to result in better deformity correction [7,8] than when correction is performed at a later age [9][10][11]. Furthermore, there is some suggestion that the use of a posterior approach alone results in a better longterm correction compared with a combined anterior/posterior approach [6,12].…”
mentioning
confidence: 99%